Las Autopromociones de Telemadrid - Victor J. Castaño Rivero; Luis M. Gándara Gil; Fidel Martínez González; Félix Martínez Martínez; Begoña Salvadores Serrano (Cuadernos de Documentación Multimedia, 2018)
Las Autopromociones de Telemadrid